Analysis of Question Representation on the Profile of Operating Ability of Elementary School Students - Ammelia, Deandra Rizka; Mariana, Neni (Journal of Innovation and Research in Primary Education, 2025)
Students' ability to solve integer operations is a fundamental aspect in basic mathematics learning. This study aims to analyze the profile of the ability of grade II elementary school students in solving number operation problems based on three forms of representation: story, numerical, and picture-based questions. The method used is qualitative descriptive with data collection techniques in the form of tests, observations, and interviews. A total of 15 students were the subjects of the study. The test results showed that the highest student success rate was found in picture-based questions (100%), followed by numerical questions (86.67%), and the lowest in story questions (23.33%). Observations indicate that students are more responsive to concrete visual representations compared to narrative forms that demand language understanding. Interviews with teachers supported these findings, citing low literacy integration and media limitations as the main causes of students' difficulties. This study concludes that the representation of questions greatly affects students' ability to solve integer operations. Mathematics learning at the initial level needs to integrate visual and literacy strategies in a balanced manner to build comprehensive problem-solving skills. These findings provide important implications for the development of learning media and curriculum design that is more adaptive to the cognitive needs of early childhood students.